A gestão escolar expressa em documentos oficiais - ALMEIDA, Jeandria Mikelly Nascimento de (2023)
This paper aims to understand the perspectives of school management expressed in official documents. Through qualitative research, based on specialized literature and documents, the article proposes the analysis of the Federal Constitution of 1988, and the Brazilian National Education Law (nº 9.394/1996), in addition to the Organic Law of the Municipality of Altamira, the Law of the Municipal Education System of Altamira (Law nº 3.085/2012) and Law of approval of Municipal Education Plan from Altamira (Law nº 3.207/2015). By debating the management perspective and identifying the management perspectives contained in the analyzed documents, it is possible to obtain a north on the steps that Brazilian education and Altamirense education have taken so that community participation in school management is a reality. It is concluded that, although democratic school management is present in all documents analyzed as a fundamental principle, there are still many issues to be overcome. Among them, the community's awareness of being present in the school management process and the breaking of the concentration of this management in the hands of schoolmasters and other figures who end up assuming a centralizing role.